The Investigation of Grammatical Category and Syntactic Position of “t͡ʃəmɑn”, a Modality Marker in Kalhori Kurdish - Tahereh Jafari; Shoja Tafakkori Rezayi (مطالعات زبان‌‌ها و گویش‌های غرب ایران)
Modality in different languages can be expressed through different grammatical categories such as modal adjectives, modal adverbs, modal auxiliaries, and modal lexical verbs. This descriptive-analytic study aims to determine grammatical category and syntactic position of “t͡ʃəmɑn” in Kalhori Kurdish, using Cinque’s spec-based approach (2004). One of the researchers’ linguistic intuition, as the native speaker of Kalhori Kurdish, was helpful in providing and analyzing the relevant data. Based on facts such as “its optional presence in the sentences”, “not receiving negative prefixes”, “not occurring with subjunctive mood”, along with “its placement necessarily after evaluative adverbs”, it was revealed that “t͡ʃəmɑn” belongs to the category of adverbs. By assuming that there is an epistemic modality projection above the tense phrase projection, the specifier of epistemic modality projection was shown to be the syntactic position of “t͡ʃəmɑn” in this language. Finally we have argued that Cinque’s spec-based approach provides an adequate framework for specifying grammatical status and explaining syntactic behavior of this linguistic element in Kalhori Kurdish. Introduction Modality in different languages is used to express a proposition and can be conveyed through various devices, such as modal adjectives, modal adverbs, modal auxiliaries, and modal lexical verbs. The purpose of this study is to determine the grammatical category and syntactic position of “t͡ʃəmɑn” as a modality marker in Kalhuri Kurdish, using Cinque’s spec-based approach (2004). Various approaches have been adopted to determine the syntactic position of adverbs. Some consider adverbs as adjuncts, which can enter the sentence structure wherever they are produced, while others believe the position of adverbs is the specifier of the projections that dominate verbal projections. In the latter approach, Cinque (2004) proposes that sentence structure consists of about thirty functional projections, with the specifiers of these projections being the syntactic positions of adverbs, including modal adverbs. In his spec-based approach, Cinque assumes a fixed position for adverbs, and the displacements that sometimes occur in the adverb order relative to other sentence constituents result from the movement of those constituents above the adverbs. Palmer (1999; 2001) considers epistemic modality a subset of propositional modality, which explains the speaker’s attitude toward the status of a proposition. The term “t͡ʃəmɑn,” meaning “as if,” appears to function as an epistemic modality adverb. The findings of this investigation may be significant for researchers studying the Kurdish language or other Iranian languages, as they explore different modality markers in relation to the thirty different kinds of projections that Cinque proposes for sentence structure, helping to determine their syntactic position. Givón (1995), Palmer (1999), and Narrog (2005) classify modality into three conceptions: it is the semantic information about the speaker’s attitude towards their speech; it extends beyond the propositions in the speech; or it is a device to distinguish truth from falsehood. These three concepts, collectively, provide a comprehensive definition of modality. Portner (2009) further defines modality as a linguistic phenomenon that enables discussion about, or based on, unreal situations. Many studies have been conducted to explore different aspects of modality. Karimi (2005) classifies adverbs into high and low adverbs. Despite proposing a linear order for adverbs, she considers them adjuncts that enter the sentence structure wherever possible. Taleghani (2008) investigated the syntactic position of “shaayad” and “baayad” in Persian, identifying "baayad" as having both epistemic and root modality meanings, while “shaayad” functions solely as an epistemic adverb. Labbafan Khosh and Darzi (2015) studied the grammatical category and syntactic position of “baayad” and “shaayad.” Considering its two different meanings, they concluded that the position of the epistemic “baayad,” like “shaayad,” is the specifier of epistemic modality, while the position of root “baayad” is the head of root modality. Materials and Methods Using a descriptive-analytic method, this research aimed to determine the grammatical category and syntactic position of “t͡ʃəmɑn” as a modality marker in Kalhuri Kurdish, according to Cinque’s spec-based approach (2004). One of the researchers, a native speaker of Kalhuri Kurdish, relied on their linguistic intuition to provide and analyze relevant data. First, based on Palmer’s classification (1999; 2001), it was established that “t͡ʃəmɑn” is an epistemic modality marker. The main analysis was divided into two parts: analyzing the grammatical category of this modality marker and determining its syntactic position. To determine the category of “t͡ʃəmɑn,” we compared its behavior with that of adverbs to establish whether it functions as an adverb. We considered several behavioral criteria, including its optional presence in the sentence, its inability to receive negative prefixes, its incompatibility with the subjunctive mood, and its required placement after evaluative adverbs. Following this, Cinque’s spec-based approach (2004) was applied to determine the syntactic position of this modal adverb. As previously mentioned, Cinque proposes that sentence structure comprises thirty different functional projections, with their specifiers serving as the positions of various kinds of adverbs. In his approach, Cinque suggests that the projection of epistemic modality dominates the tense phrase, while the projection of root modality is dominated by the tense phrase and dominates the negative phrase. The analysis then investigated the placement of “t͡ʃəmɑn” concerning this hierarchical order and, finally, examined its position as a modal epistemic adverb in relation to other words that function as the heads of root projections. Results and Discussion This study aimed to determine the grammatical category and syntactic position of “t͡ʃəmɑn” as a modality marker. Based on Palmer’s classification of mood, it was concluded that this element functions as an epistemic modality marker, which is used in certain propositions to add the meaning of "supposition" to the sentence. The analysis revealed that “t͡ʃəmɑn” shares several common features with adverbs, such as its optional presence in sentences, its inability to receive negative prefixes, its incompatibility with the subjunctive mood, and its necessary placement after evaluative adverbs. These findings indicate that “t͡ʃəmɑn” belongs to the category of adverbs. According to Cinque, the projection of epistemic modality dominates the tense phrase, while the projection of root modality is dominated by the tense phrase and dominates the negative phrase. Thus, by assuming that there is an epistemic modality projection above the tense phrase projection, it was shown that the specifier of the epistemic modality projection represents the syntactic position of “t͡ʃəmɑn” in this language. Conclusion Through the investigation of the grammatical category and syntactic position of “t͡ʃəmɑn” using Cinque’s spec-based approach, this study revealed that “t͡ʃəmɑn” is an adverb syntactically positioned in the specifier of the epistemic modality projection. The findings suggest that Cinque’s spec-based approach provides an effective framework for determining the grammatical status and explaining the syntactic behavior of this linguistic element in Kalhuri Kurdish.